The dynamics of company culture and its effect on job satisfaction for employees in Malaysia - Mathisoondan, Rajasegar (2024)
The present study investigates the effects of the dynamics of the company culture on the job satisfaction of employees within Malaysia to understand if various factors of company culture have any impact on the job satisfaction of employees. Many companies are finding difficult in holding down talents for a longer term within their organisation. The employee retention is impacted heavily as employees are looking for better opportunities in a shorter period due to the many constraints that were impacted by the pandemic. Employees are also much concern on their mental health and stress level thus looking for working environment with a better working culture. To find out if company culture impacts job satisfaction employees from various industry within Malaysia (N=51) were randomly chosen and provide a set of questionnaires to answer. The questions from the survey were made up of details regarding 3 sets of company culture. The first company culture was regarding the career development, the next company culture was management style, and the final company culture was motivational environment. The questions were set up in 5-point Likert scale were the respondents had to choose the answers with the variation from strongly agree to strongly disagree. The respondents were provided one week to complete the survey questions sent to them. The results of the survey were then compiled and analysed through the SPSS software. Through the analysis there were various results that were obtained. The results included Reliability test, Anova test, Normality test and Paired statistics. The results obtained concluded that the company culture does impact the job satisfaction of employees in a positive direction. The response from the participants confirmed that a good and positive company culture is necessary for them to maintain their job satisfaction within their working environment. Companies need to put in higher level of commitment to the company culture which are practised within their organisation.